1996
DOI: 10.1103/physreve.54.2714
|View full text |Cite
|
Sign up to set email alerts
|

Structure formation and the morphology diagram of possible structures in two-dimensional diffusional growth

Abstract: The morphology diagram of possible structures in two-dimensional diffusional growth is given in the parameter space of undercooling ⌬ versus anisotropy of surface tension ⑀. The building block of the dendritic structure is a dendrite with parabolic tip, and the basic element of the seaweed structure is a doublon. The transition between these structures shows a jump in the growth velocity. We also describe the structures and velocities of fractal dendrites and doublons destroyed by noise. We introduce a renorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
166
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 20 publications
12
166
0
Order By: Relevance
“…It is important to note that eq 3, with the boundary conditions at the interface given by eqs 1 and 4, is similar to the equation used by Müller-Krumbhaar and collaborators [10][11][12][13][14][15] 20 That is, if eq 1 would be written as…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that eq 3, with the boundary conditions at the interface given by eqs 1 and 4, is similar to the equation used by Müller-Krumbhaar and collaborators [10][11][12][13][14][15] 20 That is, if eq 1 would be written as…”
Section: Resultsmentioning
confidence: 98%
“…Apparently, we have lost the general picture given by the diffusional model proposing the existence of a diffusion zone, which with eq 7 and the boundary conditions given by eqs 1 and 2, successfully explains the pattern formation and the morphology evolution in LMs. 27,28 In the same way, apparently, we have also lost the connection with the morphology diagram with regions of different morphological structures, [6][7][8][9][10][11] determined by the control parameters ∆ and ε, as explained above. Here, we will assess in what conditions the 2D hydrodynamic eq 4 can recover that picture related to pattern formation and to the morphology diagram.…”
Section: Morphology Evolution In Langmuirmentioning
confidence: 99%
“…27,28 Our experiments agree with the kinetic morphology diagram. [6][7][8][9][10][11] However, the underlying physics involved in LM is different from the underlying physics in the Mullins-Sekerka instability; diffusional processes are not involved. This is a new kind of instability that leads to pattern formation, where Marangoni flow is the key factor.…”
Section: Introductionmentioning
confidence: 99%
“…Such a "seaweed" morphology might come about due to a competition between differently directed capillary and kinetic anisotropies. Microstructure selection maps (in undercooling-anisotropy space) produced by Brener et al [31] using solvability theory indicate a range of such transitions should occur, while simulations by Haxhimali et al [32] have suggested that many common metals may lay close to the dendritic-"seaweed" transition. One such transition has been observed directly as a function of composition in Al-Zn alloys by Dantzig et al [33].…”
Section: Introductionmentioning
confidence: 99%